Teaching Transformation of Vocational School Teachers at SMK Muhammadiyah 2 Andong under the Merdeka Curriculum: perubahan - -, Sumianto; Sayuti, Muhammad; Dahlan, M Bakrun (Bahasa Indonesia Prima, 2025)
Sumianto, Freedom of teaching and changes in how teachers teach at SMK Muhammadiyah 2 Andong, Boyolali: Faculty of Teacher Training and Education, Ahmad Dahlan University, 2024. This research aims to 1) Analyze learning models, 2) analyze changes in teacher teaching at SMK Muhammadiyah 2 Andong, and 3) analyze what factors influence changes in teacher teaching. The method used in writing this thesis is qualitative with a case study approach; data collection is collected through observation, interviews, notes, and document analysis. The participants involved teachers, the head of the curriculum, and the principal of SMK Muhammadiyah 2 Andong Boyolali. The results of this study show that teachers must develop learning in the classroom to produce high student interest in learning by: 1) Learning model. Project-Based Learning, Problem-Based Learning, Cooperative Learning, and Blended Learning. 2) The theme of teacher teaching change, creative and innovative learning, fun learning (technology-based learning, differentiated learning, discussion, e-educational learning. Learner-centered learning (student needs and interests, active learning, presentations, learning that prioritizes student needs). 3) Factors of change in teacher teaching, Teacher interest in change (Teacher enthusiasm, pride in change, teacher commitment, improving learning quality), Characteristics of the teacher.